Cybersecurity: The Security and Protection Challenges of Our Digital World. - Prince, Daniel (Computer (00189162), 2018)
Once the domain of national agencies empowered to protect civil society and support intelligence missions, cybersecurity is now the pervasive technical, social, and economic issue. It affects all aspects of our daily life and organizational functions. From financial institutions to smart homes, and from the classroom to the doctor’s office, we are in a cyber arms race to protect ourselves from those driven to do us harm.